THE REGULATION OF MONEY CIRCULATION ON THE BASIS OF USING METHODS AND INSTRUMENTS OF MONETARY POLICY - S. Mishchenko; S. Naumenkova (Вісник Київського національного університету імені Тараса Шевченка. Серія Економіка)
In the article it was researched the instruments and mechanism of safeguarding stability of money market on the basis of implementing the optimal monetary policy regime. It was determined the main directions of appliance the monetary policy methods and instruments to guiding money market stability and it was also investigated the influence of transmission mechanism on providing the soundness of money circulations.